The Mining Code for Prospecting Exploration and Exploitation in Maritime Domain: Experimenting the Regional Environmental Plans - Abdulrazaq Owolabi Abdulkadir; Saheedat O. Lawal (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2023)
The Seabed Mining is a growing maritime industrial field that involves the extraction of submerged minerals and deposits from the ocean and over the years, there has been a rising demand for minerals and metals in various sectors of the Maritime Industry. This led to the creation of the International Seabed Authority of 1982 which is saddled with the responsibilities of regulating human activities on the deep-sea floor and the continental shelf. Despite the existence of the regulatory body, there are challenges that are present within the organs of the International Seabed Authority. These challenges include lack of transparency and also the impact of the deep seabed mining activities on the environment that still need to be extensively researched before deep seabed mining activities can commence in the World Maritime Economy. This research adopted a doctrinal method of research to collect data through the use of Law textbooks, articles in journals, and various online resources. The aim of this paper is to discuss the benefits of deep seabed mining, the regulatory frameworks of deep seabed mining, the impacts of deep seabed mining on the environment, deep seabed mining activities in Africa and Nigeria. It was concluded in this paper that before the deep seabed mining activities can commence, it is necessary that wide and extensive research be carried out on its effect on the environment, the various organs in International Seabed Authority should be more transparent on their activities to the public and African States particularly Nigeria should organise workshops to educate the Maritime Industry of various states about the involvement and participation of African countries in the deep seabed mining activities like their counterparts in other countries of the World.